High Hand Contamination Rates During Norovirus Outbreaks in Long-Term Care Facilities. (14th January 2018) - Park, Geun Woo; Williamson, Keenan J.; DeBess, Emilio; Cieslak, Paul R.; Gregoricus, Nicole; De Nardo, Elizabeth; Fricker, Christopher; Costantini, Verónica; Vinjé, Jan
Abstract : We examined norovirus contamination on hands of ill patients during 12 norovirus outbreaks in 12 long-term care facilities (LTCFs). The higher frequency and norovirus titers on hands of residents compared to hands of heathcare workers highlights the importance of adhering to appropriate hand hygiene practices during norovirus outbreaks in LTCFs. Infect Control Hosp Epidemiol 2018;39:219–221